Implementasi Manajemen Sarana dan Prasarana dalam Meningkatkan Mutu Layanan Pendidikan - Hutabarat, Nurhofipah; Afriza; Agustiar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to determine the implementation of facilities and infrastructure management in improving the quality of education services at Madrasah Aliyah Nahdlatul Ulama Batangtoru, South Tapanuli Regency. The method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The results showed that the implementation of facilities and infrastructure management was carried out through three stages. First, the planning stage includes needs analysis, coordination meetings, and the preparation of budget and funding plans. Second, the implementation stage in the form of procurement, distribution, utilization, and periodic maintenance of facilities and infrastructure. Third, the evaluation stage with physical condition inspection, recording, and assessment of the effectiveness of its utilization in the learning process. Constraints found include budget limitations, lack of technical personnel, delays in fund disbursement, lack of practical space, and limited clean water. The low awareness of students in maintaining the facilities is also an obstacle. Therefore, government support is needed in the form of adequate budget, technical training, and accelerated fund disbursement. Recommendations include developing an asset information system, forming a technical team, and increasing routine maintenance to maintain the sustainability of facilities and infrastructure.